UJI POTENSI Bacillus sp. DAN Escherichia coli DALAM MENGHASILKAN INDOLE ACETIC ACID (IAA) TANPA MENGGUNAKAN TRIPTOFAN PADA MEDIA PERTUMBUHAN - Muhammad Asril (Journal of Science and Applicative Technology, 2017)
Indole Acetic Acid (IAA) is the important phytohormone for boosting plant-growth promotion. It is related with amino acid tryptophan as a precursor for building IAA. However some bacteria such as Bacillus sp. and Escherichia coli enable to produce IAA without L-tryptophan on culture medium via the tryptophan independent pathways. This study aims to determine the potential of indigenous Bacillus sp. and E. coli isolate in producing IAA via Trp-independent pathways (without L- tryptophan). The stage of this study consists of growing of isolate on liquid media without tryptophan and measuring the levels of IAA using Salkowsky method. Bacillus sp and Escherichia coli could produce IAA with the concentration of 0,0236 mmol/L and 0,024 mmol/L, respectively. The concentration of IAA produced by these bacteria is quite low because of their ability to synthesis IAA from the independent tryptophan pathway. The independent tryptophan pathway means these bacteria could synthesize IAA without using tryptophan as a precursor on their growth medium.